Tailoring the Anisotropic Oxygen Transport Properties in Bulk Ceramic Membranes Based on a Ruddlesden–Popper Oxide by Applying Magnetic Fields - Giamper Escobar Cano; Motohide Matsuda; Zhijun Zhao; Frank Steinbach; Bernd Breidenstein; Hilke Petersen; Andreas Graff; Marc Widenmeyer; Anke Weidenkaff; Armin Feldhoff (Advanced Science)
Abstract Textured Nd2NiO4+δ bulk ceramic membranes are fabricated via slip casting in a 0.9 T magnetic field generated by neodymium magnets. This process aligns the oxide grains with their easy‐magnetization c‐axis parallel to the applied magnetic field. Depending on the magnetic field's direction relative to the slip casting, grains orient either with their a,b‐plane or c‐axis parallel to the normal direction of the disk‐shaped ceramic, thus aligning with the oxygen permeation direction. Without the magnetic field, a non‐textured bulk membrane is formed. The microstructure and texture of the ceramic membranes are meticulously analyzed using advanced techniques, including X‐ray diffraction, scanning and transmission electron microscopy, as well as related methods. Evaluation of the texturing effect on the oxygen permeation performance shows that the a,b‐plane textured Nd2NiO4+δ bulk membrane achieves the highest oxygen permeation fluxes between 1023–1223 K. Additionally, it demonstrates impressive CO₂ stability, maintaining effective performance for at least 140 h due to preferential oxygen transport along the a,b‐plane. These characteristics make Nd2NiO4+δ an auspicious material for industrial applications as an oxygen transport membrane, outperforming more susceptible perovskite‐based materials. Magnetic alignment thus proves to be an effective method for achieving membrane texturing, enabling precise regulation of oxygen transport properties.